Effect of Culture Medium Supplementation with b-mercaptoethanol and Amino Acid on Canine Intergeneric Embryo Development with Porcine Oocyte Cytoplasm Recipient - Yuda Heru Fibrianto (Universitas Gadjah Mada, 2007)
The present study investigated the effect of culture medium supplementation with mercaptoethanol ( ME)and amino acid (AA) on canine intergeneric embryo development with porcine oocyte cytoplasm. Porcine cumulusoocyte complexes (COCs) were collected from slaughterhouse and matured in TCM-199 supplemented with 26.2mM NaHCO, 3.05 mM glucose, 0.91 mM sodium pyruvate, 0.57 mM L-cysteine, 75 mg/l kanamycin, 10 ng/ml 3epidermal growth factor, equine chorionic gonadotropin (eCG), 10 IU/ml human chorionic gonadotropin (hCG),and 10% (v/v) porcine follicular fluid (pFF) at 39 °C in a humidified atmosphere of 5% CO for 42-44 h and donor cell 2collected from ear skin afghanhound male dog. After somatic cell nuclear transfer (SCNT), embryo developmentwere examined for cleavage rate and 144 hr for final development after cultured in media. The result shows that,amino acid and mercapoethanol addition in culture medium (NCSU-23) have no effect on embryo development.The development rate of embryo until 16 cell stage in NCSU and NCSU supplement are 4.67% and morula stage are3.73% and 4.67%.Key words : intergeneric clone embryo, canine, ( amino acid (AA)